FINANCIAL INCLUSION THROUGH ZAKAT INSTITUTION: CASE STUDY IN INDONESIA AND BRUNEI DARUSSALAM - candra yudha, ana tony roby; Ida Wijayanti; Muhamad Nafik Hadi Ryandono; Dk Hjh Saerah Pg Hj Petra (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
This research aims to reveal the financial inclusion occurs in zakat institutions within zakat distribution and empowerment program in Indonesia and Brunei Darussalam. This study will deliver zakat distribution and empowerment program held by zakat institutions in two countries and then analyze how are financial inclusion process happened to mustahiq in both institutions. The object of this research are the government zakat institution in two countries, namely Indonesia (BAZNAS) and Brunei Darussalam (BAKAZ). This study uses a qualitative method within multiple case strategy. Data collection in this study was carried out through in-depth interviews with several expert informants of BAZNAS and BAKAZ and also mustahiq of each institutions. This study shows that there are mustahiq financial inclusion process on empowerment program held by BAZNAS and BAKAZ by distribution of zakat for consumption and production needs. Financial inclusion happened in zakat institution are transferring zakat fund, financing mustahiq business within capital loan, and channeling to financial institutions, so that mustahiq can transform gradually to be bankable and have financial access to scale up their business.